Efficiency index for fiber-reinforced concrete lining at ultimate limit state. Issue 1 (10th June 2016) - Fantilli, Alessandro P.; Nemati, Kamran M.; Chiaia, Bernardino
Abstract: The fiber contribution to the ultimate limit state capacity of precast and cast- in situ tunnel linings is analytically investigated. By means of a numerical model, capable of computing the interaction curves of reinforced concrete cross sections subjected to combined compressive and bending actions, the mechanical performances of plain and fiber-reinforced concrete are compared. As a result, a new index is introduced to quantify the effectiveness of fiber addition. The higher the efficiency index, the higher the amount of steel reinforcing bar that can be removed from a plain concrete cross section. The application to real concrete linings, where shear resistance is ensured without shear reinforcement, shows that a large volume of rebar can be saved by the presence of steel fibers. This gives significant advantages in terms of durability and rapidity of tunnel construction.